Determinanty oprocentowania kredytów w bankach komercyjnych (Część I - czynniki mikroekonomiczne) - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 1997)
The article points out the increasing importance of credit as the most essential source of bank income. This situation makes it necessary to calculate properly and scrupulously the amount of interests on bank credits. The level of interests on bank credits is an element of price strategy of a bank, the aim of which is to assure an adequate scale of services offered with, at the same time, realization of the main task of a banking enterprise, i.e. maximization of profit. There is a very large number of factors determining the price of credit. So, their influence on calculation of interests on bank credits makes it very difficult to establish clearly these interests. The factors mentioned can be classified into two groups: micro- and macroeconomic. The article discusses the following microeconomic conditions which are susceptible to influence the price of credit: costs covered by a bank, credit risk, price strategy, dimension and kind of a debtor, credit period.
Determinants factors of fixing interests on bank credits in commercial banking (Part one - Microeconomics factors)